Ultrasound-mediated diagnostic imaging and advanced treatment with multifunctional micro/nanobubbles. (10th April 2020) - Li, Jiaping; Xi, Aini; Qiao, Huanhuan; Liu, Zhe
Abstract: Ultrasound associated with ultrasound contrast agents has witnessed ever-growing innovations and applications for disease-targeted diagnosis and therapy. With these state-of-the-art technologies, brand-new invasive or minimally invasive treatments are on the way to be clinically translated. This mini-review focuses on the ultrasound and ultrasound-related micro/nanobubbles as multifunctional agents for drug/gene delivery and multi-modality treatments, e.g. photodynamic, sonodynamic and photothermal therapies in a precise and visualized manner. Highlights: The recent advanced biomedical ultrasound technologies has been summarized for their widely applications in the clinics. Gas-filled micro/nanobubbles have been classified for their versatile utilities on the diagnostic imaging and disease-targeted therapy. State-of-the-art ultrasound-based treatments as translationable strategies for fatal diseases of humans have been discussed.